АNALYSIS OF CLINICAL AND EXPERIMENTAL FORECASTING OF INFLUENCE OF ERGONOMICS OF DENTISTS WORK ON THE RESULT OF ENDONTIC TREATMENT - R.I. Ratushniy; N. Goderdzi; M.Yu. Goncharuk-Khomyn; S.B. Kostenko; I.V. Penzelyk; A.S. Chobeі (Український стоматологічний альманах, 2022)
Abstract. The ergonomic aspect of work is one of the keys to the daily practice of a dentist. In-depth study and development of ways to optimize the basic ergonomic principles of work, monitoring the dynamics of implementation and, if necessary, the possibility of their correction is an important scientific and practical issue that can increase the level of dental care.